Effects of combined nitrogen and phosphorus application on soil phosphorus fractions in alfalfa (Medicago sativa L.) production in China - Yang, Kaixin; Li, Shengyi; Sun, Yanliang; Cartmill, Andrew D.; López, Ignacio F.; Ma, Chunhui; Zhang, Qianbing (Frontiers in Plant Science, 2024)
Nitrogen (N) and phosphorus (P) fertilizers change the morphological structure and effectiveness of P in the soil, which in turn affects crop growth, yield, and quality.However, the effects and mechanism of combined N and P application on the content of P fractions and the transformation of effective forms in alfalfa (Medicago sativa L.) production is unclear. This experiment was conducted with four levels of N: 0 (N0), 60 (N1), 120 (N2) and 180 kg•ha -1 (N3); and two levels of P (P2O5): 0 (P0) and 100 kg•ha -1 (P1). The results indicated that, under the same N level, P application significantly increased soil total N, and total P, available P, and content of various forms of inorganic P when compared to no P application, while decreasing the content of various forms of organic P and pH value. In general, under P0 conditions, soil total N content tended to increase with increasing N application, while total P, available P content, pH, inorganic P content in all forms, and organic P content in all forms showed a decreasing trend.When compared to no N application, insoluble P (Fe-P, O-P, Ca10-P) of the N application treatments was reduced 2. 80 -22.72, 2.96 -20.42, and 5.54 -20.11%, respectively. Under P1 conditions, soil total N and O-P tended to increase with increasing N application, while, pH, Ca2-P, Al-P, Fe-P, Ca10-P, and organic P content of each form tended to decrease. Total P, available P, and labile organic P (LOP) of N application reduced 0. 34 -8.58, 4.76 -19.38, and 6.27 -14.93%, respectively, when compared to no application. Nitrogen fertilization reduced the soil Ca2-P ratio, while P fertilization reduced soil Fe-P, moderately resistant organic P (MROP), and highly resistant P (HROP) ratios, and combined N and P elevated the Ca8-P to LOP ratio. Soil total N content, available P content, and pH were the key factors affecting the conversion of P fractions in the soil. Nitrogen and P promoted the activation of soil organic P, resulting in accumulation of slow-acting P in the soil, thereby improving the efficiency of soil P in alfalfa production.